Answer:
3 ( x-1) (x+1) is the factored form
zeros are x=1, -1
Step-by-step explanation:
3x^2-3
Factor out a 3
3 ( x^2 -1)
What is inside the parentheses is the difference of squares
( a^2 -b^2) = ( a-b)(a+b)
3 ( x-1) (x+1)
To find the zeros, set this equal to zero
3 ( x-1) (x+1) =0
Using the zero product property
x-1 =0 x+1 =0
x=1, x=-1
So easy , two plus two equals four ahh
Answer:
Step-by-step explanation:
i got it correct:)
Answer:
The answer is C. 18 ounces
Step-by-step explanation:
You just divide the ounces by the cost and which ever you get lower is the answer
The final point should end up at (-11,-4)